Effect of treated mica on rheological, cure, mechanical, and dielectric properties of ethylene propylene diene monomer (EPDM)/barium titanate (BaTiO3)/mica. Issue 19 (23rd January 2017) - Su, Jun; Zhang, Jun
ABSTRACT: In this study, mica, treated by three types of coupling agents, isopropyl trioleic titanate (NDZ105), 3‐aminopropyltriethoxysilane (KH550), and vinyltrimethoxysiloxane homopolymer (SG‐Si6490), were utilized to improve the properties of ethylene propylene diene monomer (EPDM)/barium titanate (BaTiO3 ) composites. It is found that the addition of untreated mica can increase the complex viscosity, while the KH550 modified mica can reduce the complex viscosity. Compared to single usage of coupling agent SG‐Si6490, the hybrid usage of KH550 and SG‐Si6490 can further increase the tensile strength of EPDM/BaTiO3 /SG‐Si6490 treated mica (70/20/10) from 9.10 to 11.01 MPa (22% increase). The untreated mica can increase the interfacial polarity and improve the dielectric constant of EPDM/BaTiO3 (70/30) from 7 to 9 at 40 MHz (28% increase). Moreover, the KH550 treated mica can enhance the thermal conductivity of EPDM/BaTiO3 (70/30) from 0.323 W m −1  K −1 to 0.446 W m −1  K −1 (38% increase). In the meantime, the increased crosslink density caused by coupling agents can increase the volume resistivity of EPDM composites. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44833. Abstract :